Education as a Practice of Liberation: A Synthesis of Freire's and Habermas' Philosophical Contributions to Emancipatory Consciousness - Saeful Anwar (AIM: Journal of Islamic Education Management, 2025)
Contemporary education is increasingly co-opted by a neoliberal logic that emphasizes standards, productivity and compliance, to the exclusion of the transformational role of education. Paulo Freire and Jürgen Habermas offer philosophical frameworks capable of restoring education as a liberatory practice through the development of critical consciousness and communicative action. This study aims to synthesize the thoughts of Freire and Habermas to design an emancipatory curriculum design framework that fosters critical consciousness, democratic participation, and transformative agents in the educational context. This research uses a qualitative-philosophical approach based on conceptual analysis and critical hermeneutics. Data were collected through the study of primary texts, secondary discourses, as well as interviews and focus group discussions with educators from different levels of education. Results show that Freire's dialogical pedagogy and Habermas' communicative action can reinforce each other in creating reflective, democratic and transformative learning spaces. Participants reported increased student engagement, development of an ethic of discourse, as well as strengthening of social awareness. However, structural barriers such as rigid curriculum and evaluative pressure hinder the full implementation of this approach. The synthesis of Freire-Habermas philosophy shows significant potential in curriculum design that supports learner emancipation. Systemic reform and teacher professional development are key to realizing a more just, reflective and democratic vision of education.